Electrochemistry in magnetic fields - Luo, Songzhu (2022)
Developing new strategies to advance the fundamental understanding of electrochemistry is crucial to mitigating multiple contemporary technological challenges. In this regard, magnetoelectrochemistry offers many strategic advantages in controlling and understanding electrochemical reactions that might be tricky to regulate in conventional electrochemical fields. However, the topic is highly interdisciplinary, combining concepts from electrochemistry, hydrodynamics, and magnetism with experimental outcomes that are sometimes unexpected. In this Review, we survey recent advances in using a magnetic field in different electrochemical applications organized by the effect of the generated forces on fundamental electrochemical principles and focus on how the magnetic field leads to the observed results. Finally, we discuss the challenges that remain to be addressed to establish robust applications capable of meeting present needs.